The necessity for and use of CDMA transmitter filtering in overlay systems. - Rainbolt, B.J (IEEE Journal on selected areas in communications)
The concept of code division multiple access (CDMA) overlay has been proposed as a way to take advantage of the unused bandwidth available in sparsely populated narrowband systems. Most research up to this point has focused on the effects of the narrowband system on the CDMA system. However, because the CDMA system is likely to be overlaid on a narrowband system that is already established, it is of equal or greater importance to examine how the CDMA overlay would affect the narrowband system's performance. It is shown that even a lightly loaded CDMA system can have a detrimental effect on a narrowband system to the point where the possibility of overlay may be precluded. To solve this problem, the idea of notch filtering the CDMA signals in an effort to avoid those bands already occupied by narrowband users is examined. For certain filtering methods the effects of CDMA interference on the narrowband system are shown to be greatly reduced, thus making overlay feasible from the perspective of the narrowband system. For the CDMA system, the performance of the minimum mean-squared error (MMSE) receiver was evaluated and it was found to work quite well with CDMA signals that have been notched. With CDMA transmitter filtering, the prospects for overlay become very encouraging